PFG NMR measurements of tortuosity factors for diffusion in meso- and macropores of FCC catalysts - Vasenkov, Sergey; Kortunov, Pavel (Diffusion Fundamentals, 2005)
Pulsed field gradient (PFG) NMR is applied to measure self-diffusion coefficients of 1,3,5 tri-isopropyl-benzene in the particles of several industrial FCC catalysts having different systems of meso- and macropores. Relating these diffusivities to the self-diffusion coefficient of 1,3,5 tri-isopropyl-benzene in the liquid phase, the tortuosity factors for diffusion in the meso- and macropores of the particles were obtained. The values of the tortuosity factors were found to increase with a increasing volumetric fraction of the small (< 20 nm) meso- and macropores in the total intraparticle volume.